Upaya Peningkatan Kemampuan Guru Dalam Menyusun Silabus Dan RPP Melalui Supervisi Akademik Di SD 101772 - Mhd Nuryansyah Nugraha; Putri Rizky; Raya Marcela; Usna Aulia; Safran Safran (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research aims to determine efforts to improve teachers' abilities in compiling syllabuses and lesson plans through academic supervision. This research was conducted at SDN 101772 Tanjung Selamat, the subjects of this research were teachers at SDN 101772 Tanjung Selamat. The method used in this research is a descriptive qualitative method, data collection techniques are carried out through observation, interviews and documentation. The results of the research show that the quality of the syllabus and lesson plans made by the teachers at SDN 101772 can be said to be poor. This is because there are still many syllabi and lesson plans that still use the old format and don't seem original. In the assessment of the syllabus and lesson plans that have been implemented, many weaknesses were still found. They are late to the instant culture by copying the syllabus and RPP models developed by the Central Government.